2006
DOI: 10.1029/2005jc003333
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the South China Sea associated with El Niño

Abstract: [1] Interannual sea surface temperature (SST) anomalies in the South China Sea (SCS) are largely influenced by El Niño through El Niño-driven atmospheric and oceanic changes. This paper discovers a new observed feature of the SCS SST anomalies: a double-peak evolution following an El Niño event. The first and second peaks occur around February and August, respectively, in the subsequent year of the El Niño year (denoted by February [+1] and August [+1]). During and after the mature phase of El Niño, a change o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
171
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(187 citation statements)
references
References 17 publications
14
171
0
2
Order By: Relevance
“…The change of mixed layer depth (MLD) is also an important factor that impacts the SST [84], and in turn SST can impact the atmospheric circulation. The interannual variability of SST in the SCS has a distinct bimodal structure: the El Niño-related warming in February and August in the following year, and the mean meridional geostrophic heat advection of the SCS are the main factors that lead to the second warming in August [85]. Most previous studies suggested that the interannual variability of SST in the SCS is closely related to the wind change, and little research concerned the SCSWBC influence on the SST.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…The change of mixed layer depth (MLD) is also an important factor that impacts the SST [84], and in turn SST can impact the atmospheric circulation. The interannual variability of SST in the SCS has a distinct bimodal structure: the El Niño-related warming in February and August in the following year, and the mean meridional geostrophic heat advection of the SCS are the main factors that lead to the second warming in August [85]. Most previous studies suggested that the interannual variability of SST in the SCS is closely related to the wind change, and little research concerned the SCSWBC influence on the SST.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…In the SCS, the interannual variability of mean sea level (MSL) exhibits a strong signature of ENSO due to intrusion of the Kuroshio Current through the Luzon Strait, coupled with atmospheric teleconnection (Qu et al, 2004;Wang et al, 2006;Cheng and Qi, 2007;Rong et al, 2007;Chen et al, 2012;Tkalich et al, 2013;Peng et al, 2013;Nidheesh et al, 2013). The correlation with ENSO becomes stronger towards the southern part of the SCS (Rong et al, 2007;Peng et al, 2013).…”
Section: Q H Luu Et Al: Sea Level Trend and Variability Around Penmentioning
confidence: 99%
“…At the same time, the SCS covers both tropical and subtropical areas, and is close to the WPWP, so that the SST, humidity, cloudiness, and monsoon winds are strongly influenced by the ENSO (Wang et al 2006). During the El Niño phase of ENSO, the SCS has a positive SST anomaly and a precipitation deficit (Xu et al 2004;Wang et al 2006). In addition, the SCS summer monsoon rainfall may be closely related to the PDO and ENSO over interdecadal timescales, such that a high PDO/El Niño (low PDO/La Niña) phase pattern is associated with reduced (above-normal) monsoon rainfall (Chan and Zhou 2005).…”
Section: Study Sitesmentioning
confidence: 99%
“…Conversely, the seasurface circulation during the winter monsoon season is characterized by a cooling of surface waters (Wang and Wang 1990). At the same time, the SCS covers both tropical and subtropical areas, and is close to the WPWP, so that the SST, humidity, cloudiness, and monsoon winds are strongly influenced by the ENSO (Wang et al 2006). During the El Niño phase of ENSO, the SCS has a positive SST anomaly and a precipitation deficit (Xu et al 2004;Wang et al 2006).…”
Section: Study Sitesmentioning
confidence: 99%